Cellular and molecular mechanism of cardiac regeneration: A comparison of newts, zebrafish, and mammals - de Wit, Lousanne; Fang, Juntao; Neef, Klaus; Xiao, Junjie; Doevendans, Pieter A.; Schiffelers, Raymond M.; Lei, Zhiyong; Sluijter, Joost P.G. (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Cardiovascular disease is the leading cause of death worldwide. Current palliative treatments can slow the progression of heart failure, but ultimately, the only curative treatment for end-stage heart failure is heart transplantation, which is only available for a minority of patients due to lack of donors' hearts. Explorative research has shown the replacement of the damaged and lost myocardium by inducing cardiac regeneration from preexisting myocardial cells. Lower vertebrates, such as the newt and zebrafish, can regenerate lost myocardium through cardiomyocyte proliferation. The preexisting adult cardiomyocytes replace the lost cells through subsequent dedifferentiation, proliferation, migration, and re-differentiation. Similarly, neonatal mice show complete cardiac regeneration post-injury; however, this regenerative capacity is remarkably diminished one week after birth. In contrast, the adult mammalian heart presents a fibrotic rather than a regenerative response and only shows signs of partial pathological cardiomyocyte dedifferentiation after injury. In this review, we explore the cellular and molecular responses to myocardial insults in different adult species to give insights for future interventional directions by which one can promote or activate cardiac regeneration in mammals.
Keywords: cardiac regeneration; cardiomyocyte dedifferentiation; proliferation; cardiomyocyte polyploidy; Biochemistry; Molecular Biology; Journal Article; Review